Empathy and the ability to experience one's own emotions modify the expression of blatant and subtle prejudice among young male adults. (May 2021) - Önal, A.; Rapp, M.A.; Sebold, M.; Garbusow, M.; Chen, H.; Kuitunen-Paul, S.; Montag, C.; Kluge, U.; Smolka, M.N.; Heinz, A.
Abstract: Prejudices can lead to discrimination, social exclusion, and violence particularly among young male adults. Previous findings suggest that the degree of holding prejudices is linked to low levels of empathy, while low levels of empathy have been associated with alexithymia, the inability to experience one's own feelings. We tested the hypothesis that the impact of a lack of empathy on reporting blatant and subtle prejudices is moderated by the inability to identify one's own feelings. In a sample of n = 136 young male adults aged 21 years (mean = 21.5 years; sd = 0.3), we conducted correlation and moderator analyses to determine possible relationships between prejudices, empathy, and alexithymia as assessed by self-report questionnaires. Prejudices were assessed by the Blatant and Subtle Prejudice Scale (BSPS), empathy was assessed by the German modified version of the Interpersonal Reactivity Index (IRI), and alexithymia by the 20-item Toronto Alexithymia Scale (TAS-20). Self-reported empathy levels were correlated with the strength of subtle and blatant prejudices. The moderation analyses revealed that the negative association between empathy and subtle prejudice increased with decreasing alexithymia. The negative association between empathy and blatant prejudice, on the other hand, was significant only for participants with low levels of alexithymia. These results suggest that empathy can limit the expression of blatant and to some degree also subtle prejudice when subjects are capable to identify their own feelings in a group of young males.